(untitled) (Vietnam Journal of Community Medicine, 2025)
The toxicity of material M1 used for production of Jasmin detox, a dietary supplement containing powdered Jasminum subtriplinerve, Silybum marianum, Centella asiatica, Solanum procumbens, and Cynara scolymus as main ingredients, has been evaluated in acute and sub-chronic toxicity studies. Acute oral toxicity studies in ICR mice did not detect mortality or treatment-related signs at a dose of 5000 mg/kg/24h for 72h (LD50 >5000 mg/kg). Dose selection for sub-chronic toxicity studies of LD50 (500 mg/kg). After continuous administration of M1 for 28 days at this dose, treated mice presented no significant change in body weight, in daily behaviors and weight of selected organs (liver, spleen, and kidney) as well. The hematological parameters, liver indices (ALT level), renal indices (creatinine level) were not affected. The study showed that materials to produce Jasmin detox capsules are safe to be taken orally at a dose of 500 mg/kg bd.w for 28 days.